Gastroduodenal mucosa in uraemia: endoscopic and histological correlation and prevalence of helicobacter-like organisms. Issue 10 (October 1990) - Wee, A; Kang, J Y; Ho, M S; Choong, H L; Wu, A Y; Sutherland, I H
Abstract : This study aimed to determine the prevalence of endoscopic and histological gastroduodenitis as well as helicobacter-like organisms in patients with end stage renal failure undergoing maintenance dialysis treatment. A total of 322 out of 422 patients in our dialysis programme underwent endoscopy and gastroduodenal biopsy specimens were taken from 260. Endoscopic gastroduodenitis occurred in 158 (49%). Histological gastritis occurred in the gastric body or antrum in 134 patients (52%) and duodenitis in 52 (21%). There was no correlation between endoscopic and histological gastritis in contrast to a significant correlation for duodenitis. Helicobacter-like organisms occurred in the body or antrum in 81 (31%). Their presence was associated with gastritis--in particular acute and acute on chronic gastritis rather than chronic gastritis. Patients with gastritis were significantly older than those without (p less than 0.001) and had lower basal and peak acid outputs.